Carlo Baja Guarienti, “Il bandito e il governatore. Domenico d'Amorotto e Francesco Guicciardini nell'età delle guerre d'Italia“, Viella, 2014, 235 p., ISBN 978-88-6728-208-1 - COTOI, Paula (Studia Universitatis Babeș-Bolyai Historia, 2015)
The work of the young researcher Carlo Baja Guarienti, published in 2014, represents the outcome of his doctoral research, finished seven years ago. Guarienti is currently a professor of Modern History at the Department of Humanist Studies form Ferrara University. This is the institution where he obtained his BA in Classical Studies and later completed his PhD in models, languages and traditions in Western culture. The PhD thesis, Francesco Guicciardini e il bandito Amorotto. Poteri e culture in conflitto nella Reggio del Cinquecento, as well as the articles and studies published in scientific journals in recent years, reveal Guarienti’s deep knowledge of his subject matter, based on both successive accumulations and refined understanding of this area of investigation.